DESIGN OF A CONTROL SYSTEM TO ENHANCE PROCESS PERFOMANCE IN THE PRODUCTION OF SORGHUM BEER - Catherine Maware; Norman Gwangwava; Raphel M Jingura (European Scientific Journal, ESJ, 2013)
The quality of products produced over the years has been the major concern for many industries. In brewing, the introduction of automated brewing systems has helped to reduce the variability of beer produced. The reasons for introducing the automated systems are to reduce energy usage and the batch processing time by increasing equipment utilization. The main aim of the paper is to design a control system that helps in monitoring and controlling the mashing process, temperature and monitor the water level that is put in the cookers during sorghum beer brewing. The research carried out showed that companies in Zimbabwe use dry bulb thermometers to measure the temperature of mash in the cooker. The companies also have no level measurement sensors that would measure the amount of water that would be poured into the cooker to primarily cool the mash. The design of the control circuit was done using sensors and controllers. For controlling the temperature a PID controller was used. The model for the temperature control system was build and processed in the identification tool box from the Matlab environment. The mash was raised to 50˚C for 50minutes and the hydrolysis of protein, β glucons and pentasons by proteolic enzymes. The temperature was then raised to 80˚C and maintained constant for 10minutes at this stage for the optimal activity of β-amylase. It was then raised to 95˚C for the optimal activity of α- amylase. Finally, the temperature was raised to 100˚C and held constant for 60minutes for enzyme inactivation